EDUKASI FAKTOR RISIKO DISARTRIA (GANGGUAN BICARA) PADA LANSIA DARI SEKOLAH LANSIA SALIMAH ARCAMANIK BANDUNG - Karina Tikavona; Revalina Alexandra Claudia; Fasya Chairunnisa Muttaqin; Neny Widyana (JURNAL PENGABDIAN KEPADA MASYARAKAT (ADI DHARMA), 2026)
Speech disorders that occur in the elderly, especially dysarthria,are a problem that causes impaired communication skills and a decline in quality of life due to neurological disorders.The elderly's lack of knowledge about risk factors and early signs of dysarthria often leads to delays in early intervention. This study aims to provide education on the risk factors for dysarthria and to assess the effectiveness of education in improving the knowledge of the elderly. This activity was carried out using a lecture method through verbal means, interactive discussions and question and answer sessions, as well as video screenings and facial exercise simulations. There were 30 elderly participants from the Salimah Elderly School, Arcamanik, Bandung, who participated in this activity. The results of the t-test on the pre-test and post-test showed significant values marked by a p-value of less than 0.05, namely 0.03. This indicates that the education provided was effective in increasing the knowledge of the elderly.